Run, Rose, run : [compact disc, unabridged] a novel - Parton, Dolly; Patterson, James, 1947- (Hachette Audiobook, 2022)
A singer on the rise is also on the run from the hard life behind her. Nashville is where she has come to claim her destiny. It's also where the darkness that she fled might find her. If it does, it will destroy her.